(untitled) (Journal of Computational Mathematics, 2021)
For the nonlinear system x=g(x)+h(x)+c, xR^n, where g and h are isotone and antitone mappings respectively, a two-sided interval iterative method is presented, the initial condition of the two-sided iterative method is relaxed, and the convergence of the two methods are proved.